MAR 21 and cataloguing of Arabic materials - Suja', Balqis (2009)
This is a two-hour presentation to introduce young librarians to the rules applicable for cataloguing the Arabic materials and materials originating from Arabic resources. Besides aspects of romanisation, Arabic names and Arabic genres, participants were enlightened on how MARC 21 works on bibliographic relationships, collocation and OPAC display. The lecture ended with a brief group exercise on how to record details from translated works of Arabic.